Introduction - Barton, B; Redgwell, C; Rønne, A; Zillman, D (Oxford University Press, 2010)
This chapter begins by discussing how people's reliance on energy made clear the importance of energy security. It then discusses the history of energy use, security, and imposed geopolitical risk. It also discusses the concept and characteristics of energy security, and mentions several issues in energy security among nations. It provides a brief description of all the chapters discussed in this book.